A two-photon fluorescent probe for colorimetric and ratiometric monitoring of mercury in live cells and tissues - Chen, Liyan; Park, Sang Jun; Wu, Di; Kim, Hwan Myung; Yoon, Juyoung (Chemical Communications, 2019)
Owing to the extreme toxicity of mercury, methods for its selective and sensitive sensing in solutions, and in live cells and tissues are in great demand. In this study, we developed a naphthalimide-based diphenylphosphinothioyl group-containing fluorescent and colorimetric probe that selectively detects mercury (Hg2+). Upon addition of mercury (Hg2+) to a solution of the probe, both a colorimetric change from colorless to yellow and a fluorescence change from blue to green (under a 365 nm hand-held UV lamp) occur, both of which can be observed using the "naked-eye". Furthermore, the probe possesses the capability of sensing intracellular mercury in both live cells and tissues using dual-emission channels and two-photon microscopy.
Keywords: Fluorescent Dyes; HeLa Cells; Humans; Mercury; Microscopy, Fluorescence, Multiphoton; Naphthalimides; Spectrometry, Fluorescence